Ensuring Legal Protection for Civil Servants in Government Procurement: Reducing Criminalization Risks Through Strengthened Administrative Oversight and Accountability Frameworks - Fera Julia Rahman; AA Sagung Laksmi Dewi (Journal of Law, Society and Living Norms, 2026)
This study examined the legal protection afforded to civil servants involved in Government Goods and Services Procurement and assessed how regulatory and institutional safeguards could reduce the growing trend of administrative errors being treated as criminal offenses. Using a normative juridical approach supported by statutory interpretation, doctrinal analysis, and interviews with procurement practitioners, the Research Identified a Persistent Mismatch Between The Legal Framework and Its Implementation. Although procurement regulations formally placed early-stage oversight under the Government Internal Supervisory Apparatus (APIP), law-enforcement bodies frequently intervened before administrative review was completed, resulting in summonses and investigations that created a deterrent effect among procurement officials. The findings showed that clearer distinctions between administrative, civil, and criminal liability, combined with reinforced APIP authority and accessible alternative dispute-resolution mechanisms, would enhance legal certainty for civil servants and stabilize procurement performance. This study provided theoretical refinement to the concept of accountability in procurement law and offered practical recommendations for strengthening institutional safeguards to prevent unwarranted criminalization.